PERLINDUNGAN HUKUM TERHADAP INVESTOR UNTUK MENGHINDARI KERUGIAN AKIBAT PRAKTEK MANIPULASI PASAR DALAM PASAR MODAL - Endra Bayu Sudiartha, Kadek; Subawa, Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013)
The title of this legal research is legal protection of investors to avoid losses due to market manipulation practices in the capital market. Legal protection is needed because the capital markets are also violations or criminal offenses in the field of capital markets that could harm those who participate in the capital markets. Capital market in any country prone to market manipulation. The tricks in stock trading is a lot of variety. Unfortunately, not all of the tricks that the negative tendency can be detected by law. The purpose of this study was to determine the form of legal protection of investors and the measures to prevent market manipulation in the stock market. The research method used in this paper is the empirical legal research. Based on the results of the study it was concluded that this form of investor protection is the protection of the law against indirectly by applying the principles of openness and protection directly to the protection of securities and funds owned by the investor. measures to prevent market manipulation practices are preventive, in the form of rules, guidelines, guidance, and supervision.
Keywords: Capital markets, investors, market manipulation, legal protection